Kemampuan Serbuk Daun Nangka (Artocarpus heterophyllus Lamk) Dalam Menekan Serangan Nematoda Puru Akar (Meloidogyne Spp.) Pada Tanaman Seledri - Yuliana, Maria; Marsuni, Yusriadi; Fitriyanti, Dewi (JURNAL PROTEKSI TANAMAN TROPIKA, 2025)
Celery (Apium graveolens L.) is a leafy vegetable that plays a very important role and has significant export value. In terms of popularity and economic value, celery ranks second after lettuce among spice plants. In South Kalimantan, celery is widely cultivated, but there are serious obstacles faced by farmers, namely the attack of root knot nematodes (Melodogyne spp.) whose population is quite high. Celery plants infected with Meloidogyne spp. usually shows symptoms such as chlorosis on the leaves, stunted growth, wilted leaves, and a small number of roots. In severe conditions, the plant may die. Therefore, the search for environmentally friendly alternatives for pest control is very important. The aim of this research is to reduce dependence on chemical pesticides which can damage agricultural ecosystems. One alternative that can be considered in controlling pests is the use of vegetable pesticides derived from jackfruit leaves (Artocarpus heterophyllus Lamk). This research aims to test the effectiveness of jackfruit leaf powder in dealing with attacks by root knot nematodes (Meloidogyne spp.) on celery plants which is the main focus of this research. This research was carried out by applying the Completely Randomized Design (CRD) method, which aims to obtain accurate and reliable data regarding the impact of the attack which involves one factor, namely treatment using 500 Meloidogyne spp eggs. as a control and four other treatments with jackfruit leaf powder: 500 Meloidogyne spp. + 25 grams of jackfruit leaf powder (P1), 500 Meloidogyne spp eggs. + 50 grams of jackfruit leaf powder (P2), 500 Meloidogyne spp eggs. + 75 grams of jackfruit leaf powder (P3), as well as 500 Meloidogyne spp eggs. + 100 grams of jackfruit leaf powder (P4). The results of the research showed that treatment with 100 grams of jackfruit leaf powder (P4) was able to reduce the severity of the disease and the average number of root knot nematode populations. The highest disease severity was recorded in control plants (K0), namely 38.80%, while the lowest percentage was found in the treatment (P4) which only reached 12.50%. The highest root knot nematode population was observed in treatment (P1) with 427.25 individuals, while the lowest population was recorded in treatment (P4) with 199,875 individuals.